The effects of nature-based interventions on individuals’ environmental behaviors: protocol for a systematic review of controlled trials - Šorytė, Dovilė; Rosa, Claudio D.; Collado, Silvia; Pakalniškienė, Vilmantė (Frontiers in Psychology, 2023)
Background: The paper presents the rationale and methods of the planned systematic review to understand the effects of nature-based interventions on individuals’ environmental behaviors. There is ample evidence that experiences in nature not only enhance human well-being but also help promote people’s pro-environmentalism. Nevertheless, synthesized evidence regarding the effects of nature-based interventions on individuals’ environmental behaviors is lacking. Methods: This protocol follows the Preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) guidelines. The planned literature search will be conducted by using APA PsycInfo, APA PsyArticles, PubMed, ERIC, Education Source, GreenFILE, OpenDissertations, Scopus, and WEB of Science. In the protocol, we present search strategies for each specific database. Data items that we will seek to obtain from the selected publications are described in detail and cover general information about included studies, information about studies’ methodology and participants, outcomes of the studies, and nature-based and comparative interventions. The outcomes will be behavioral, including aggregated and specific types of environmental behaviors, as well as reported and observed behaviors. Furthermore, the protocol provides a description of the prospective assessment of the risk of bias in both randomized and non-randomized studies. If studies appear sufficiently homogeneous, we will conduct meta-analyses using the inverse-variance method. Details of the data synthesis are likewise provided in the paper. Results: Dissemination of the results of the planned review will be carried out via a peer-reviewed open-access journal publication. Implications: Given the great need to address current environmental issues, understanding what encourages people to act pro-environmentally is critical. It is expected that the findings of the planned review will provide valuable insights for researchers, educators, and policymakers who are involved in understanding and promoting human environmental behaviors.